(NoPASNYE GIDROMETEOROLOGI^ESKIE QWLENIQ NA kAWKAZE (B/s - (NaBDU[ELI[WILI(B, (Nk(B.(Nl(B.s; (NgAGUA(B, (Nw(B.(Np(B.s; (NkERIMOW(B, (Na(B.(Na(B.s; (NsWANIDZE(B, (NgIWI gEDEONOWI^s; (NcUCKIRIDZE(B, (Nq(B.(Na(B.s; (NzAKAWKAZSKIJ NAU^NO(B-(NISSLEDOWATELXSKIJ GIDROMETEOROLOGI^ESKIJ INSTITUTs ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1980)
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NgIDROMETEOROLOGI^ESKIE NABL@DENIQs